Evaluation of Intubating Conditions during Direct Laryngoscopy using Sniffing Position and Simple Head Extension- A Randomised Clinical Trial - Amanjot Singh (JCDR Research and Publications Private Limited, 2021)
Introduction: Optimal laryngeal visualisation during direct laryngoscopy requires adequate positioning of the head and neck. Traditionally, Sniffing Position (SP) is the recommended position to provide superior glottic visualisation. However various studies in recent past have challenged the superiority of SP. Aim: To evaluate whether SP provides better glottic visualisation and ease of intubation {as assessed by total Intubation Difficulty Score (IDS) score as well as its individual components} compared to Simple Head Extension (SHE) during direct laryngoscopy and endotracheal intubation. Materials and Methods: The randomised clinical trial was conducted at GGS Medical College and Hospital, Faridkot, Punjab, India, from May 2019 to October 2020, on 220 patients. Patients undergoing elective surgeries under general anaesthesia were randomly divided into two groups. Laryngoscopy and tracheal intubation in Group I was done in SP, which was obtained by placing a non compressible pillow of height 8 cm under the patient’s head. Patients in Group II underwent laryngoscopy and tracheal intubation in SHE position. Glottic visualisation using modified Cormack and Lehane (CL) grades, IDS and sympathetic responses between the two groups were studied. The data was compared using student’s t-test and Chi-square test. Results: Cormack and Lehane Grade I was seen in 69 (62.7%) of patients in Group I as against 51(46.4%) of patients in Group II (p-value=0.015). Easy intubation (total IDS score=0) was seen in a greater number of patients in Group I (60.9%) as compared to Group II (40.95%) (p-value=0.003). Slight difficulty in intubation (total IDS score=1-5) was encountered in 50.0% of patients in group II (n=55) and 35.5% of patients in group I (n=39) (p-value=0.029). Conclusion: The present study concluded that use of SP resulted in better glottic visualisation and was associated with favourable intubation conditions as compared to SHE position.